Oxazolidinone resistance genes in florfenicol-resistant enterococci from beef cattle and veal calves at slaughter - Nüesch-Inderbinen, Magdalena; Biggel, Michael; Haussmann, Adrian; Treier, Andrea; Heyvaert, Lore; Cernela, Nicole; Stephan, Roger (Frontiers in Microbiology, 2023)
Background: Linezolid is a critically important oxazolidinone antibiotic used in human medicine. Although linezolid is not licensed for the use in food-producing animals, the use of florfenicol in veterinary medicine co-selects for oxazolidinone resistance genes. Objective: This study aimed to assess the occurrence of cfr, optrA and poxtA in florfenicol-resistant isolates from beef cattle and veal calves from different herds in Switzerland. Methods: A total of 618 cecal samples taken from beef cattle and veal calves at slaughter originating from 199 herds were cultured after an enrichment step on a selective medium containing 10 mg/L florfenicol. Isolates were screened by PCR for cfr, optrA and poxtA which are genes known to confer resistance to oxazolidinones and phenicols. One isolate per PCR-positive species and herd was selected for antimicrobial susceptibility testing (AST) and whole genome sequencing (WGS). Results: Overall, 105 florfenicol-resistant isolates were obtained from 99 (16%) of the samples, corresponding to 4% of the beef cattle herds and 24% of the veal calf herds. Screening by PCR revealed the presence of optrA in 95 (90%), and poxtA in 22 (21%) of the isolates. None of the isolates contained cfr. Isolates included for AST and WGS analysis were Enterococcus (E.) faecalis (n=14), E. faecium (n=12), E. dispar (n=1), E. durans (n=2), and E. gallinarum (n=1), Vagococcus (V.) lutrae (n=2), Aerococcus (A.) urinaeequi (n=1), and Companilactobacillus (C.) farciminis (n=1). Thirteen isolates exhibited phenotypic linezolid resistance. Three novel OptrA variants were identified. Multilocus sequence typing identified four E. faecium ST18 belonging to hospital-associated clade A1. There was a difference in the replicon profile among optrA and poxtA harboring plasmids, with rep9(RepA_N) plasmids dominating in optrA-harboring E. faecalis and rep2(Inc18) and rep29(Rep_3) plasmids in poxtA-carrying E. faecium. Conclusions: Beef cattle and veal calves are reservoirs for enterococci with acquired linezolid resistance genes optrA and poxtA. The presence of E. faecium ST18 highlights the zoonotic potential of some bovine isolates. The dispersal of clinically relevant oxazolidinone resistance genes throughout a wide variety of species including Enterococcus spp., V. lutrae, A. urinaeequi and the probiotic C. farciminis in food-producing animals is a public health concern.